1932
DOI: 10.1001/archotol.1932.03570030207002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic Properties of the Secretions of the Sinuses

Abstract: The normal secretions of the sinuses is a grayish, viscous fluid that bathes the entire lining membrane, protecting it and assisting the ciliated epithelium in the removal of foreign substances. The physical properties of this fluid and its r\l=o^\lein the protection of the sinuses have been studied by Yates,1 Walthard 2 and Stark.3 Bacteriologic observations by T\l=o"\rne,4 Frankel,5 Calamida and Bartarelli,6 and Linton7 indicate that the normal nasal sinus is usually sterile. The important r\l=o^\le played b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This, however, was not immediately appreciated. The earliest studies, beginning in 1896, found airway surface liquid to be sterile or nearly so; when added to agar plates, few or no microbial colonies formed (42). Investigators also failed to detect bactericidal activity in nasal secretions (82).…”
Section: Antimicrobialsmentioning
confidence: 99%
“…This, however, was not immediately appreciated. The earliest studies, beginning in 1896, found airway surface liquid to be sterile or nearly so; when added to agar plates, few or no microbial colonies formed (42). Investigators also failed to detect bactericidal activity in nasal secretions (82).…”
Section: Antimicrobialsmentioning
confidence: 99%